2016
DOI: 10.18860/ling.v10i2.3261
|View full text |Cite
|
Sign up to set email alerts
|

Digital Native: A Study on the First-Year Student

Abstract: The digital native generation emergent triggers the educational practitioner to develop a new way of approaching the teaching practice in the classroom. As it is claimed that this generation has a unique characteristics and way of learning. Therefore, this paper explore the experience of the first year student of English language and letters department in using technology. Students were asked about their access to, use of and preferences for a wide range of established and emerging technologies and technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This media was developed considering that digital literacy and competence are currently needed to support the characteristics of students as digital native figures. This group of students is advised to use technology in their daily lives extensively, thus requiring more technology involved in the learning process (Nur Rakhmawati & Kusuma, 2016) (Chang & Lai, 2021) their research also revealed that the Immersive Experience achieved by students allowed them to practice repeatedly without the supervision of an instructor and allowed students to practice skills repeatedly without using any equipment. Through the STELAR Application, students can continue to practice related skills that are currently needed in the field of office administration, namely managing archives, especially archives in a digital environment.…”
Section: Resultsmentioning
confidence: 99%
“…This media was developed considering that digital literacy and competence are currently needed to support the characteristics of students as digital native figures. This group of students is advised to use technology in their daily lives extensively, thus requiring more technology involved in the learning process (Nur Rakhmawati & Kusuma, 2016) (Chang & Lai, 2021) their research also revealed that the Immersive Experience achieved by students allowed them to practice repeatedly without the supervision of an instructor and allowed students to practice skills repeatedly without using any equipment. Through the STELAR Application, students can continue to practice related skills that are currently needed in the field of office administration, namely managing archives, especially archives in a digital environment.…”
Section: Resultsmentioning
confidence: 99%
“…Rakhmawati and Kusuma found that more research is needed to determine the related factors which affect students’ perspectives move from “living technology” toward “learning technologies.” They emphasized based on other similar literature that this transition is neither automatic nor guaranteed. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, students nowadays are among digital natives where they are more familiar with the use of technology such as using gadgets and surfing the internet in their daily life [28]. Hence, educators need to be more up-to-date in the advancement of technology used in education and they also have to be more advanced than the students.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%